In vitro antibacterial activity of medicinal Lucilia cuprina larvae (Diptera: calliphoridae) against selected pathogenic bacteria / Teh Chien Huey - Teh, Chien Huey (2012)
Maggot Debridement Therapy (MDT) is a type of biosurgery involving the intentional application of live, disinfected fly larvae into the chronic non-healing wounds of human or animal to debride the necrotic tissue and disinfect the infected wounds. Many studies have demonstrated the potent antibacterial activity of Lucilia sericata larval excretions/secretions against bacteria, however, the antibacterial activity of the local strain of blowfly, L. cuprina (Wiedeman) larval extract against bacteria has never been determined, although MDT using L. cuprina larvae was successfully conducted. In view of this, the objectives of this study are to develop a procedure for the production of sterile L. cuprina larval extract as well as to study the in vitro antibacterial activity of L. cuprina larval extract against seven selected potentially pathogenic wound bacteria: Staphylococcus aureus, Methicillin-resistant Staphylococcus aureus (MRSA), Staphylococcus epidermidis, Streptococcus pyogenes, Klebsiella pneumoniae, Pseudomonas aeruginosa and Escherichia coli. Larvae were sterilized using established procedures and sterile larval extract was produced successfully via subsequent methanol-homogenization of larvae, centrifugation of homogenate and vacuumconcentration of the resultant supernatant. The vacuum-concentrated product (larval extract) was kept at -70°C and re-suspended in sterile distilled water prior to use. Turbidometric (TB), Colony-Forming Units (CFU), Agar Well-Diffusion and Minimum Inhibitory Concentration (MIC) assays were adopted to determine the in vitro antibacterial activity and properties (bactericidal and/or bacteriostatic) of larval extract against the seven selected bacteria. TB Assay has demonstrated significant growth inhibition of all bacteria tested (p<0.001). However, both CFU and well-diffusion assays have demonstrated the significant potent inhibitory effect of L. cuprina larval extract towards P. aeruginosa and these results were substantiated by the MIC assay that as little as 0.78 mg/ml of larval extract was able to inhibit at least 50% of the growth of P. aeruginosa. L. cuprina larval extract has proven to withstand long-term storage (13 months) and was thermally stable. In conclusion, the highly robust L. cuprina larval extract exhibited broad-spectrum antibacterial activity and was particularly potent against the Gram-negative bacteria.